Francisco Aguilar Piñal, Un escritor ilustrado: Cándido María Trigueros. CSIC, Madrid, 1987; 370 pp., 8 láms. - Álvarez Barrientos, Joaquín (El Colegio de México, 1989)
Se reseñó el libro: Un escritor ilustrado: Cándido María Trigueros.